Segmental Assessment of Trunk Control in Moderate-to-Late Preterm Infants Related to Sitting Development - Noppharath Sangkarit; Orawan Keeratisiroj; Ponlapat Yonglitthipagon; Surussawadi Bennett; Wantana Siritaratiwat (MDPI AG, 2021)
(1) Background: The assessment of postural segment control in premature infants seems to be critical during the onset of upright gross motor development, especially sitting. Identifying correlations between postural segment control and the development of sitting milestones could help with promoting optimal gross motor movement. However, data on this topic in home-raised premature infants via longitudinal design are still limited. The purpose of this study was to examine relationships between postural segment control and sitting development through series assessments from the corrected age of 4 months until the early onset of independent sitting attainment. (2) Methods: 33 moderate-to-late premature infants were recruited. Their trunk segment control was assessed using the Segmental Assessment of Trunk Control (SATCo), and sitting development was examined by the Alberta Infant Motor Scale (AIMS). Relationships between SATCo and sitting scores were analysed using Spearman's rank correlation (rs). (3) Results: significant fair-to-good correlations between segmental trunk control and sitting scales were found from 4 months (rs = 0.370-0.420, p < 0.05) to the age of independent sitting attainment (rs = 0.561-0.602, p < 0.01). (4) Conclusion: relationships between the trunk segment control and sitting ability of moderate-to-late preterm infants were increased in accordance with age.